2019
DOI: 10.1021/acs.cgd.9b00843
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal Heterojunction Integration via Template-Assisted Selective Epitaxy

Abstract: We report on the successful integration of multiple atomically thin horizontal heterojunctions (HJs) epitaxially grown via metal organic chemical vapor deposition inside a confined template of dielectric material. InAs, GaAs, and InGaAs layers were included in laterally grown InP structures and characterized to show abrupt interfaces and crystalline material. The orientation of the templates and the substrate is chosen so that a flat vertical facet appears at the growth front allowing for the HJs to be horizon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Further studies to finetune the epitaxial processes are ongoing. We note that using a similar geometry on a InP substrate the growth of sharp and vertical quantum wells was demonstrated [31,32]. Fig.…”
Section: Resultsmentioning
confidence: 82%
“…Further studies to finetune the epitaxial processes are ongoing. We note that using a similar geometry on a InP substrate the growth of sharp and vertical quantum wells was demonstrated [31,32]. Fig.…”
Section: Resultsmentioning
confidence: 82%
“…Advantages of using gold catalyst free nanowire growth are: 1) removing the catalyst from the process, making it more complementary metal-oxide semiconductor compatible by removing risk of gold-related deep level doping of silicon, [59] and 2) the possibility of making abrupt junction transitions along the nanowire. [60] A disadvantage is the atomic layer defects often seen in gold-free nanowire growth, such as twin planes, stacking faults, or polytypism, [53] which potentially could affect performance for some devices. However, a study by Zhuang et al using indium droplet assisted growth showed how a 2-4 at% inclusion of antimony (Sb) in indium arsenide (InAs) nanowires, generated quasi-pure WZ structure, whereas a 10 at% inclusion generated quasi-pure ZB structure.…”
Section: Inas Nanowires From Directed Self-assemblymentioning
confidence: 99%
“…It can represent a single solution for the integration of all major photonic components [12,13] such as, photodetectors [12,14], emitters [15,16], modulators, and waveguides. While TASE structures grown with a single growth facet have been reported on III-V substrates [17,18], a multifaceted end surface is the most common situation for structures grown on Si [9,11,[19][20][21]. This is not inherently an issue for binary III-V microstructures.…”
Section: Introductionmentioning
confidence: 99%